2013
DOI: 10.1111/jan.12223
|View full text |Cite
|
Sign up to set email alerts
|

Observation charts with overlapping blood pressure and heart rate graphs do not yield the performance advantage that health professionals assume: an experimental study

Abstract: These findings suggest that overlapping graphs do not yield the performance advantage that many health professionals assume, either for novices or experienced nurses, even when the Seagull Sign is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Focus groups were scheduled during shift overlap, staff development sessions and education forums to enable as many staff as possible to attend. An interview schedule guided discussion with items based on a review of the literature and from evaluations of early chart versions22 24 29 33 34 (see box 1).
Trigger questions for semistructured focus groups

How did you find using the new charts?

…”
Section: Methodsmentioning
confidence: 99%
“…Focus groups were scheduled during shift overlap, staff development sessions and education forums to enable as many staff as possible to attend. An interview schedule guided discussion with items based on a review of the literature and from evaluations of early chart versions22 24 29 33 34 (see box 1).
Trigger questions for semistructured focus groups

How did you find using the new charts?

…”
Section: Methodsmentioning
confidence: 99%
“…Vital signs data are generally recorded on paper charts placed at the end of the patients’ beds or in their rooms. These processes are subject to potential error and/or failure, such as inadequate monitoring frequency,1–3 5 10–12 incomplete data,1 10 13 inaccurate calculations of early warning score (EWS),14–17 and poor legibility and interpretability of charts,18 19 all of which have been implicated in the failure to recognise, or respond to, patient deterioration 1–3 5…”
Section: Introductionmentioning
confidence: 99%
“…A more recent experimental study has demonstrated that abnormal blood pressure and heart rate observations can be detected more quickly and accurately when these two vital signs are plotted separately, especially on charts with an integrated colour‐based early‐warning scoring‐system (Christofidis et al . ). However, no empirical study to date has directly assessed the effects of other individual observation chart design features on the detection of patient deterioration.…”
Section: Introductionmentioning
confidence: 97%
“…In Christofidis et al . 's () experiment, overlapping blood pressure, and heart rate plots actually impeded recognition of abnormal vital signs by experienced nurses and novice chart‐users alike, slowing them down and increasing their error rates. It has been suggested that performance‐preference dissociations like this arise due to the inordinate influence of extraneous factors, such as familiarity and aestheics, on people's judgements and preferences (Andre & Wickens ).…”
Section: Introductionmentioning
confidence: 99%